Gene expression and locomotor recovery in adult rats with spinal cord injury and plasma-synthesized polypyrrole/iodine application combined with a mixed rehabilitation scheme - Coyoy-Salgado, Angélica; Orozco-Barrios, Carlos; Sánchez-Torres, Stephanie; Olayo, María Guadalupe; Cruz, Guillermo Jesus; Morales-Corona, Juan; Olayo, Roberto; Diaz-Ruiz, Araceli; Ríos, Camilo; Alvarez-Mejia, Laura; Mondragón-Lozano, Rodrigo; Morales-Guadarrama, Axayacatl; et al. (Frontiers in Neurology, 2023)
Introduction Spinal cord injury (SCI) can cause paralysis, for which effective therapeutic strategies have not been developed yet. The only accepted strategy for patients is rehabilitation (RB), although this does not allow complete recovery of lost functions, which makes it necessary to combine it with strategies such as plasma-synthesized polypyrrole/iodine (PPy/I), a biopolymer with different physicochemical properties than PPy synthesized by conventional methods. After SCI in rats, PPy/I promotes functional recovery. Therefore, the purpose of this study was to increase the beneficial effects of both strategies and identify which genes activate PPy/I when applied alone or in combination with a mixed scheme of RB by swimming and enriched environment (SW/EE) in rats with SCI. Methods Microarray analysis was performed to identify mechanisms of action underlying the effects of PPy/I and PPy/I+SW/EE on motor function recovery as evaluated by the BBB scale. Results Results showed robust upregulation by PPy/I in genes related to the developmental process, biogenesis, synapse, and synaptic vesicle trafficking. In addition, PPy/I+SW/EE increased the expression of genes related to proliferation, biogenesis, cell development, morphogenesis, cell differentiation, neurogenesis, neuron development, and synapse formation processes. Immunofluorescence analysis showed the expression of β-III tubulin in all groups, a decreased expression of caspase-3 in the PPy/I group and GFAP in the PPy/I+SW/EE group (p < 0.05). Better preservation of nerve tissue was observed in PPy/I and PPy/SW/EE groups (p < 0.05). In the BBB scale, the control group scored 1.72 ± 0.41, animals with PPy/I treatment scored 4.23 ± 0.33, and those with PPy/I+SW/EE scored 9.13 ± 0.43 1 month after follow-up. Conclusion Thus, PPy/I+SW/EE could represent a therapeutic alternative for motor function recovery after SCI.